النظائر المخادعة بين الكلمات الأتشيهية والعربية والاستفادة منها في تعليم اللغة العربية للأتشيهين - Aditya, Abdul Hadi; Sani, Ahmad (Institut Agama Islam Negeri Lhokseumawe, 2023)
The researcher chose the title about al-Nazhair al-Mukhadi'ah with the hope of being able to make it easier for Arabic teachers to teach their students.al-Nazhair al-Mukhadi'ah are words that have the same pronunciation but different meanings. This study aims to find the amountal-Nazhair al-Mukhadi'ah between Acehnese and Arabic as well as showing differences in the pronunciation of the sentences and showing how to use them in teaching Arabic to the Acehnese people. Researchers in compiling this research using descriptive analysis research method, where with this method researchers can describe al-Nazhair al-Mukhadi'ah between Acehnese and Arabic and explains the forms of similarities and differences between the two languages ​​and explains how to use them in teaching Arabic. the results of the study found that there were 56 al-Nazhair al-Mukhadi'ah between Acehnese and Arabic.al-Nazhair al-Mukhadi'ah Those words are found in the Aceh-Indonesian dictionary from the letters A-J then combined with Mu'jam al-Wasith. Among 56 al-Nazhair al-Mukhadi'ah In this case, there are some words that sound the same and some have slight differences. Some of the vocabulary there are those that are often spoken by the Acehnese people in their daily conversations and some are rarely spoken. As for how to use al-Nazhair al-Mukhadi'ah in teaching Arabic to the people of Aceh is to give the task of memorizing the Arabic vocabulary that has been found, then making active sentences from each memorized vocabulary.